Electrical power cable engineering - Thue, William A. (Power engineering., 2012)
"Fully updated, this third edition addresses the design, application, and preparation of terminating and splicing cables. The book provides methods for testing shielded power cable systems in the field, and it shows how conductor material, size, and design depend on ampacity, voltage regulation, and other factors. It also covers the up-to-date methods of design, manufacture, installation, and operation of power cables. Written for professionals as well as students, this book emphasizes low and medium voltages because they comprise the quantity of cable in service throughout the world. This reference includes an extensive glossary, as well as key references, tables, equations, and photographs"--